THE FLUENCE OF SHOPEE’S DOUBLE DATE DISCOUNTS ON THE CONSUMPTIVE BEHAVIOUR OF COMMUNICATION SCIENCE STUDENTS AT UNIVERSITY SRIWIJAYA, CLASS OF 2023 - Indrianita, Nadira; Zahra, Syarifah; Razaq, Abdur; Nugraha, Muhamad Yudistira (Laboratorium Pembelajaran Bahasa, FKIP Universitas Lampung, 2025)
This research aims to analyze the effect of Shopee's